The Neuroeducation: Creativity and Motivation in Education - Ochoa Rosas, Erika; Espinosa Ramírez, Rafael Salvador (Ciencia y Reflexión, 2026)
Talking about neuroeducation is your topic. Although it may seem new, teachers have already used it in classrooms for some years, even if they have not called it by that name. Teachers implement strategies from neuroeducation in neurodidactics, where they apply techniques to enhance students’ learning. However, only in recent years have researchers begun to recognize the importance of neuroscience and psychology in the learning process, which has opened a clearer view of the brain’s role in educational institutions. This research seeks to promote the applicability of creativity and motivation as part of neuroeducation in different educational settings. The study uses a qualitative and descriptive methodology and includes 30 participants randomly selected from a population of 110. The researchers conducted interviews with various stakeholders in the educational field from different countries through distance learning. One of the most significant findings is that, within the category of motivation, neuroeducation revealed that, by having good self-esteem, students enhance their academic trajectory